2016
DOI: 10.1073/pnas.1615872113
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow synthesis of ZSM-5 zeolite on the order of seconds

Abstract: The hydrothermal synthesis of zeolites carried out in batch reactors takes a time so long (typically, on the order of days) that the crystallization of zeolites has long been believed to be very slow in nature. We herein present a synthetic process for ZSM-5, an industrially important zeolite, on the order of seconds in a continuous flow reactor using pressurized hot water as a heating medium. Direct mixing of a well-tuned precursor (90°C) with the pressurized water preheated to extremely high temperature (370… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Another possible route for further reducing the growth duration is by making use of the accelerated growth kinetics at an elevated temperature similar to what was demonstrated recently for the crystallization of the zeolite ZSM-5. 56…”
Section: Resultsmentioning
confidence: 99%
“…Another possible route for further reducing the growth duration is by making use of the accelerated growth kinetics at an elevated temperature similar to what was demonstrated recently for the crystallization of the zeolite ZSM-5. 56…”
Section: Resultsmentioning
confidence: 99%
“…(a) An effective seeding to avoid aging stage and heterogeneous nucleation, (b) a well‐tuned synthesis precursor to enable fast crystal growth, (c) fast heating to avoid decomposition of the organic structure‐directing agent, and (d) high temperature to accelerate the crystal growth rate of the target structure . Another approach was proposed by the same group using pressurized hot water (370°C) to increase the reaction mixture temperature (240°C‐300°C). They demonstrated, for the first time, the crystallization of ZSM‐5 zeolite in the order of seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous flow processes having high solid contents are susceptible to hydrodynamic failures caused by constriction, bridging, and random detachment of solid particles . Liu et al proposed a compressed‐air‐driven vibrator to minimize precipitation or blockage problems. Continuous oscillatory baffled reactors/crystallizers (COBR/COBC) have been used in processes where a crystallization step is involved .…”
Section: Introductionmentioning
confidence: 99%
“…This has led to innovative studies that report efficient methods to produce zeolites in short period of time. [28][29][30][31] Temperature, a signicant factor in zeolite syntheses that govern the rate of nucleation and crystal growth is crucial for shortening the synthesis time of zeolites, which would otherwise take several days to even weeks. Hitherto, the complexity surrounding the zeolite formation mechanism remains unexplained and many studies have suggested that in fact, it is the nucleation that consumes much time rather than the crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, the complexity surrounding the zeolite formation mechanism remains unexplained and many studies have suggested that in fact, it is the nucleation that consumes much time rather than the crystal growth. [30][31][32][33][34] Recently, the ultrafast synthesis techniques that involves tubular reactor with the assistance of seed that reduces the synthesis time of zeo-type and zeolites viz., AFI, CHA, MFI, ERI, and MOR down to several minutes were reported by us. 30,[35][36][37][38][39][40][41][42] Table S1 † compares the experimental conditions of these zeolites with the current study.…”
Section: Introductionmentioning
confidence: 99%